Sistema de gestión en seguridad informática como soporte a la toma de decisiones en respuesta a incidentes, basados en monitoreo de redes - Armijos Guevara, Ariel (2011)
NetSolutioncompany specializing in the networking area which will provide consulting, implementation, training and tool holders with security policies based on network services. The most common problems companies face and have every day. Internet use by unauthorized users, Internet easily via virus infections, high availability database, network services servers insecure and unprotected, spam, email high availability, protection of local and remote attacks, in failure or system down there monitoring tools and alerts. The proposal to solve the problems described above are: Have monitoring tools alert on events that break the security policies and business continuity, ensuring the security policies and access restrictions on the use of network services and business customers, create Internet access policies by schedules and customer groups, have antivirus software for servers to protect information. Generate Incident Reports, risks and failures, ensuring the availability of network services such as internet, database, e-mail of the organization.